RESISTANCE OF ATMOSPHERIC AND COLD CELLULAR CONCRETE - Jalolov Zayniddin; Sodiqjon Khakimov Namangan (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
The article focused on the literature of scientists who worked on the resistance of cellular concrete to cold and atmospheric conditions